Clinical evidence supporting cranberry as a complementary approach to Helicobacter pylori management. Issue 3 (16th September 2020) - Howell, Amy B.
Abstract: This concise review summarizes results of the latest clinical trials that support the use of standardized cranberry juice intake as a complementary means of suppressing Helicobacter pylori infections. While not a replacement for antibiotic therapies, this tolerable and accessible dietary approach to help reduce inoculum levels in high‐risk populations could help curb infections and potentially reduce antibiotic use and subsequent stomach cancer prevalence.